PURINE AND PYRIMIDINE CONTENTS OF SOME DESOXYPENTOSE NUCLEIC ACIDS - Daly, M. M. (The Rockefeller University Press, 1950)
The distribution of purines and pyrimidines in desoxypentose nucleic acids prepared from a variety of animal and plant sources has been studied. 1. The nucleic acids were prepared from calf thymus, calf kidney, sheep spleen, horse spleen, chicken erythrocyte, turtle erythrocyte, trout sperm, shad testes, sea urchin sperm, wheat germ, and Pneumococcus Type III. 2. Separate hydrolyses were carried out for the determination of purines and pyrimidines. These procedures permitted nearly quantitative recovery of nucleic acid phosphorus in many of the preparations examined. 3. In the case of those preparations where a quantitative recovery was obtained it can be concluded that no bases other than adenine, guanine, thymine, and cytosine were present in appreciable amounts. 4. The distribution of purines and pyrimidines in all the nucleic acids studied renders the tetranucleotide hypothesis untenable. 5. The results of the analyses have indicated no great differences in the composition of these nucleic acids with respect to purines and pyrimidines.